Stress Corrosion Cracking and Localized Corrosion Properties of 7020 Aluminum Alloy under Cl- Environment and Their Correlation Analysis - LUO Xian-fu, LIU Xiao-yong, ZHANG Wen-li, ZHA Xiao-qin, ZHANG Heng-kun (Cailiao Baohu, 2021)
In order to further recognize the corrosion behaviors of aluminum alloy in Cl--contained environment, the means of immersing experiment, metallographic observation, polarization curves measurement, slow strain rate tension, scanning electron microscope and transmission electron microscope were employed to study the localized corrosion, stress corrosion cracking(SCC)performance and the correlation between the localized corrosion and the stress corrosion of 7020 aluminum alloy.Results showed that 7020 aluminum alloy had little local corrosion sensitivity immersed in 3.5% NaCl solution at 50 ℃ for 24 h.On the contrast, the local corrosion sensitivity increased when the sample was immersed in 3.5% NaCl +0.5% H2O2 solution at 50 ℃ for 24 h.Moreover, the stress corrosion sensitivity of the alloy in 3.5% NaCl + 0.5% H2O2 solution was lower than that of the 3.5% NaCl solution at 50 ℃.Due to the difference of the external environment, there was no specific correlation between the localized corrosion and the stress corrosion of 7020 alloy when the Cl- concentration was constant.